2005
DOI: 10.1152/ajplung.00061.2005
|View full text |Cite
|
Sign up to set email alerts
|

Anionic poly(amino acid)s dissolve F-actin and DNA bundles, enhance DNase activity, and reduce the viscosity of cystic fibrosis sputum

Abstract: . Anionic poly(amino acid)s dissolve F-actin and DNA bundles, enhance DNase activity, and reduce the viscosity of cystic fibrosis sputum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 27 publications
2
64
0
Order By: Relevance
“…These gel-forming mucins are primarily responsible for the rheological properties of airway mucus (2). However, in disease states such as CF and chronic bronchitis, polymeric DNA and filamentous actin, two products of leukocyte lysis, contribute greatly to, and are the principal determinants of, the viscoelastic properties of the purulent sputum that is associated with these diseases (3,4). The molecular weights of mucins range between 2×10 6 Da and 40×10 6 Da, and they are composed of 50% to 85% carbohydrate (5)(6)(7).…”
Section: Mucinsmentioning
confidence: 99%
“…These gel-forming mucins are primarily responsible for the rheological properties of airway mucus (2). However, in disease states such as CF and chronic bronchitis, polymeric DNA and filamentous actin, two products of leukocyte lysis, contribute greatly to, and are the principal determinants of, the viscoelastic properties of the purulent sputum that is associated with these diseases (3,4). The molecular weights of mucins range between 2×10 6 Da and 40×10 6 Da, and they are composed of 50% to 85% carbohydrate (5)(6)(7).…”
Section: Mucinsmentioning
confidence: 99%
“…Previous studies of DNA, F-actin [43], alginate [44], and other anionic filaments present at sites of infection confirm the generality of these biophysical arguments and suggest strategies for design of cationic amphiphiles with reduced binding to linear polyelectrolytes without loss of targeting to bacterial surfaces [45]. Even strong inhibition of cationic antibacterial peptide activity by DNA, F-actin, Medical Studies/Studia Medyczne 2017; 33/2 or other natural negatively charged biopolymers was observed in vitro [1][2][3][4][5][6]; their interaction with NETs is much more complex within in vivo settings. Some reports suggest that DNA release from neutrophils represents an innate immune response to trap, maintain, and buffer the release of cationic defence molecules in exact time-space where the pathogens are trapped.…”
Section: Condensation Of Dna By Cationic Peptidesmentioning
confidence: 88%
“…The statement that the presence of eDNA is crucial for the biofilm formation and structural integrity is additionally established by the reports demonstrating that the treatment with DNase 1 reduces the attachment of microbial cells to the surface, inhibits the biofilm development, and reduces the mass of mature biofilm [65], which is determined by the impairment of cell-to-cell adhesion and joining elements in microbial aggregates [66,67]. Importantly, the co-administration of antimicrobial agents with factors that have the ability to disassemble the biofilm polyelectrolyte network, including DNase 1, considerably improves their antibacterial efficiency [5,68]. As well as the reports indicating the vital role of eDNA in the biofilm structure, it was demonstrated that eDNA acts as an agent affecting the neutrophilmediated response and triggering the phagocytosis.…”
Section: Dna and F-actin In Bacterial Biofilm Developmentmentioning
confidence: 96%
See 2 more Smart Citations